KEPASTIAN HUKUM WILAYAH KERJA PENGUSAHAAN PANAS BUMI EX KONTRAK OPERASI BERSAMA DIENG DAN PATUHA DALAM KERANGKA PERIZINAN PANAS BUMI DI INDONESIA: Legal Certainty Of Geothermal Concession Working Area Ex Joint Operation Contract Of Dieng And Patuha In The Framework Of Geothermal Licensing In Indonesia - Defrizal, Defrizal; Zaenal Muttaqien; Rudi Kurniawan (Faculty of Law, Trisakti University, 2023)
Legal certainty in the area of geothermal energy exploitation is very important to ensure the sustainability of geothermal operations in Indonesia. One interesting case to be analyzed is the joint operation contract in the Dieng and Patuha areas. Legal certainty regarding geothermal licensing in these areas has a significant impact on investment and the development of geothermal technology in Indonesia. This study aims to find out the legal status of the Decree of the Minister of Energy and Mineral Resources No. 2789 K/30/MEM/2012 and Minister of Energy and Mineral Resources Decree No. 2192K/30/MEM/2014 reviewed with the licensing theory and legal certainty theory. This study uses a normative legal method with a juridical-normative approach. The results found that the legal product from the geothermal authority in the form of a Decree of the Minister of Energy and Mineral Resources concerning Affirmation of the Working Area for Geothermal Resources Concession has an impact on the absence of legal certainty even though the existing regulations are sufficient to regulate geothermal permits. This should be an urgency to implement laws that apply as a form of guaranteeing absolute legal certainty. Keywords: Geothermal, Licensing, Dieng-Patuha, Legal Certainty, Urgency